Guanabenz Downregulates Inflammatory Responses via eIF2α Dependent and Independent Signaling - Takigawa, Shinya (Int J Mol Sci, 2016)
Integrated stress responses (ISR) may lead to cell death and tissue degeneration via eukaryotic translation initiation factor 2 α (eIF2α)-mediated signaling. Alleviating ISR by modulating eIF2α phosphorylation can reduce the symptoms associated with various diseases. Guanabenz is known to elevate the phosphorylation level of eIF2α and reduce pro-inflammatory responses. However, the mechanism of its action is not well understood. In this study, we investigated the signaling pathway through which guanabenz induces anti-inflammatory effects in immune cells, in particular macrophages. Genome-wide mRNA profiling followed by principal component analysis predicted that colony stimulating factor 2 (Csf2, or GM-CSF as granulocyte macrophage colony stimulating factor) is involved in the responses to guanabenz. A partial silencing of Csf2 or eIF2α by RNA interference revealed that Interleukin-6 (IL6), Csf2, and Cyclooxygenase-2 (Cox2) are downregulated by guanabenz-driven phosphorylation of eIF2α. Although expression of IL1β and Tumor Necrosis Factor-α (TNFα) was suppressed by guanabenz, their downregulation was not directly mediated by eIF2α signaling. Collectively, the result herein indicates that anti-inflammatory effects by guanabenz are mediated by not only eIF2α-dependent but also eIF2α-independent signaling.